Evaluating campaign quality : can the electoral process be improved? - Maisel, Louis Sandy, 1945- (Communication, society, and politics., 2007)
For a number of years, voters and academic observers have been dissatisfied with a number of elements of American campaigns. Contemporary races are seen as too negative, too superficial, and too unfair or misleading. Based on these complaints, a variety of reform organizations have targeted millions of dollars to improve the situation. Through their efforts and those within the academic community, a wide range of reform initiatives have been undertaken, such as voluntary codes of conduct, industry self-regulation, certificate programs, tougher ethics rules for consultants, and the encouragement of more substantive venues. This book seeks to evaluate whether these activities have improved the level of campaign discourse and conduct in US House and Senate campaigns and argues that while individual reform efforts have achieved some of their stated objectives, the overall effect of these reform efforts has been disappointing.